2004
DOI: 10.4315/0362-028x-67.11.2538
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Heat Synergism for Inactivation of Alicyclobacillus acidoterrestris Spores in Citrus Juice

Abstract: The objective of this study was to investigate the influence of electron-beam and gamma-ray irradiation and temperature (85 to 95 degrees C) on Alicyclobacillus acidoterrestris GD3B strain (NCIMB 13137) spores by calculating and comparing the decimal reduction dose or time (D-values). The survival rate of A. acidoterrestris spores decreased exponentially with irradiation doses of an electron beam or gamma ray. D-values determined for electron-beam and gamma-ray irradiated spores on filter paper ranged from 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In a subsequent report, Lee and others () studied the effect of the SSC (or water activity, osmotic pressure) on the inactivation of spores of A. acidoterrestris by combining heat and HHP, and they drew the same conclusion as Sokołowska and others () that there was hardly any inactivation effect at high SSC, such as 70 °Brix. Nakauma and others () found that irradiation (electron beam) at a certain dose can enhance the effect of heating, and by testing the inactivation of A. acidoterrestris spores in dextrin, the authors indicated that the irradiation of powdered ingredients in combination with thermal treatment of the juice may be a new and advantageous method to control Alicyclobacillus .…”
Section: Combined Intervention Treatmentsmentioning
confidence: 99%
“…In a subsequent report, Lee and others () studied the effect of the SSC (or water activity, osmotic pressure) on the inactivation of spores of A. acidoterrestris by combining heat and HHP, and they drew the same conclusion as Sokołowska and others () that there was hardly any inactivation effect at high SSC, such as 70 °Brix. Nakauma and others () found that irradiation (electron beam) at a certain dose can enhance the effect of heating, and by testing the inactivation of A. acidoterrestris spores in dextrin, the authors indicated that the irradiation of powdered ingredients in combination with thermal treatment of the juice may be a new and advantageous method to control Alicyclobacillus .…”
Section: Combined Intervention Treatmentsmentioning
confidence: 99%
“…Nakauma et al (28) reported that D-values (radiation doses) for electron-beamand gamma-irradiated A. acidoterrestris spores on filter paper were 1.02 and 1.10 kGy, respectively. Nakauma et al (28) reported that D-values (radiation doses) for electron-beamand gamma-irradiated A. acidoterrestris spores on filter paper were 1.02 and 1.10 kGy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A lthough gam m a irradiation has been applied to various fruit juices to control foodborne pathogenic bacteria (14,30) and bacterial spores (28), the effects o f this treatm ent on therm oacidophilic spores suspended in juice concentrates apparently have not been studied. T he main objective o f this study was to investigate the effect of gam m a irradiation on A. acidoterrestris spores in apple and orange juices o f various concentrations and to evaluate changes in pH, w ater activity, and color o f juice concentrates.…”
mentioning
confidence: 99%
“…Thus, these authors proposed the use of 1% calcium hydroxide instead of 20 000 mg/mL chlorine, which currently is recommended as a sanitizer for alfalfa seeds intended for sprout production. Nakauma et al (2004) studied the influence of electron-beam and gamma-ray irradiation (1.02 to 1.10 kGy) and temperature (85 to 95uC) to inactivate Alicyclobacillus acidoterrestris spores. To this end, the decimal reduction dose or time were compared for single methods and the combined method.…”
Section: New Industrial Sterilization Technologiesmentioning
confidence: 99%